R-SUPPORTS IN TENSOR TRIANGULATED CATEGORIES - Grigory Garkusha (Journal of Algebra and Its Applications, 2010)
Various authors classified the thick triangulated ⊗-subcategories of the category of compact objects for appropriate compactly generated tensor triangulated categories by using supports of objects. In this paper we introduce R-supports for ring objects, showing that these completely determine the thick triangulated ⊗-subcategories. R-supports give a general framework for the celebrated classification theorems by Benson–Carlson–Rickard–Friedlander–Pevtsova, Hopkins–Smith and Hopkins–Neeman–Thomason.